PENGARUH PEMBELAJARAN AKTIF BERBANTUAN KARTU SUKU KATA TERHADAP MEMBACA PERMULAAN SISWA SEKOLAH DASAR - Fransisca Ayu Prasetyo Murti; Muhtarom (STKIP Subang, 2026)
Early reading ability is a crucial cognitive foundation for lower-grade elementary school students, but its acquisition is often suboptimal due to conventional passive learning paradigms. This study aims to investigate the effect of active learning strategies assisted by syllable card media on the early reading skills of first and second-grade elementary school students. This quantitative study utilized a quasi-experimental design. The research instruments were systematically validated through expert judgment by 5 peers and empirically tested on a field sample of 30 students. Evaluation of instrument quality integrated Classical Test Theory (SPSS) and Modern Test Theory via the Rasch Model using Ministep 5.1.5.2 software. Content validation yielded an Aiken's V index ranging from 0.67 to 0.93, confirming that all structural items were valid. Inter-rater reliability analysis demonstrated a high level of internal consistency with a Cronbach's Alpha coefficient of 0.805, robustly supported by a Fleiss' Kappa coefficient of 0.684, which indicates a substantial and statistically significant agreement among raters (p = 0.000). Furthermore, the modern Rasch analysis verified measurement stability with a Person Reliability index of 0.71 and an Item Reliability index of 0.74, with all item parameters classified as fit within the measurement model (Infit/Outfit MNSQ ranges of 0.82–1.28). In conclusion, the developed assessment model meets strict psychometric standards, and the implementation of active learning significantly accelerates basic literacy acquisition in the foundational phase of primary education.